2016
DOI: 10.1016/j.tig.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Breaking TADs: How Alterations of Chromatin Domains Result in Disease

Abstract: Spatial organization is an inherent property of the vertebrate genome to accommodate the roughly 2m of DNA in the nucleus of a cell. In this nonrandom organization, topologically associating domains (TADs) emerge as a fundamental structural unit that is thought to guide regulatory elements to their cognate promoters. In this review we summarize the most recent findings about TADs and the boundary regions separating them. We discuss how the disruption of these structures by genomic rearrangements can result in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
296
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(316 citation statements)
references
References 97 publications
10
296
0
3
Order By: Relevance
“…Compelling examples were recently published in which 3C studies decisively helped to unravel the molecular mechanisms underlying disease (Lupianez et al 2016).…”
Section: Explaining Disease In the 3d Genomementioning
confidence: 99%
“…Compelling examples were recently published in which 3C studies decisively helped to unravel the molecular mechanisms underlying disease (Lupianez et al 2016).…”
Section: Explaining Disease In the 3d Genomementioning
confidence: 99%
“…Moreover, the mother does not have conspicuous facial features, which is concordant with the fact that the 7q11.23 inversion may not involve severe clinical symptoms [Tam et al, 2008]. However, it has been recently demonstrated that the disruption of the 'topologically associating domain', i.e., distant and separated regions of the genome that share the same enhancers, promoters, and transcriptional machinery by chromosomal rearrangements, can cause gene misexpression and disease [Lupiáñez et al, 2016]. Thus, this situation could explain the clinical suspicion of a lower IQ but a normal physical phenotype in the mother.…”
Section: Discussionmentioning
confidence: 65%
“…22 Different juxtapositions of transcription factories, enhancers, and promoters interact with each other in physical space, giving rise to differential expression patterns. 23,24 Such variation in chromosomal conformation is not only found among different organisms, but is also observed among different tissues of the same organism. Distinct cell types exhibit unique 3D chromatin structures and genome topology.…”
Section: Chromosomal Conformation Codementioning
confidence: 99%
“…25 Altering the structure of TADs and boundaries can lead to diseases. 24 Notably, 3D genome structure modifications play a central role in cell identity determination for other mechanisms such as transcriptional and epigenetic control, the details of which will be expanded in the following sections.…”
Section: Chromosomal Conformation Codementioning
confidence: 99%